PENGARUH LINGKUNGAN KOS TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN GEOGRAFI (STKIP) PGRI SUMATERA BARAT - Efendi, Jaswir; Suarto, Edi; Erita, Yeni (STKIP PGRI Sumbar, 2013)
This research purpose to getting information, analyzing, and discuss data about the effect of environment boarding house towards achievement study studentsÂ Geography STKIP PGRI West Sumatra.Kind research used co relational descriptive. Population research is all of studentsâ geography number of 655 people. The sample research taken with Random Sampling proportion sample determined 10% so that sum of research sample is 66 students.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Based on analyze simple regression linear, fold (multiple) and correlation then sum up as follow:(1) Â there are the effect of environment boarding house towards achievement study Â studentsÂ Geography STKIP PGRI West Sumatra because t-calculate > t-table was Â (3,393 > 1,668), the effect of environment boarding house who live towards achievement study is low categories Â Â Â Â Â Â (r = 0,390) and big contribution environment boarding house included minor (15,2%), (2) there are the effect number of students which cost in the one bedroom towards achievement study studentsÂ Geography STKIP PGRI West Sumatra because t-calculate > t-table was (3,624 > 1,668). Significant effect number of students which cost in the one bedroom towards achievement study included middle Â Â Â Â Â Â Â Â (r = 0,413) and big contribution number of students that cost in the one bedroom towards achievement study is very small that is 17,0% and (3) there are the effect of environment costâs students and number of studentsâ cost in the one bedroom towards achievement study studentsÂ Geography STKIP PGRI West Sumatra with contribution both variable costâ environment mentioned toward variable Y number ofÂ 24,9% included categories small and variable costâ environment students and number of studentsâ cost determining achievement study studentsÂ Geography STKIP PGRI West Sumatra.